Characterization of anisotropic hardening of AA3003-O. Issue 1 (1st December 2022) - Lou, Y; Chen, Z; Zhang, C; Jiang, N; Yang, G
Abstract : This research aims to characterize the anisotropic hardening behaviour AA3003-O under uniaxial tension by experiments and analytical modelling. Experiments are conducted with dogbone specimens along different loading directions under quasi-static conditions to characterize the strain hardening behavior of the alloy under different loading conditions. Experimental results show the strong anisotropic hardening behaviour of the alloy under uniaxial tension along different directions. The anisotropic hardening behaviour is analytically characterized by the Yld2000-2d, Stoughton-Yoon2009 and a newly proposed anisotropic hardening models. The analytical predicted yield surfaces are compared with experiments and other constitutive models. It demonstrates that the proposed functions provide the best accuracy for the modelling of anisotropic hardening behaviour of uniaxial tension along different directions.